Space, perspective and public preaching. Reconstructing the role and functionality of public squares in the Latin Levant: the case of famagusta (Northern Cyprus) - Borowskia, Tomasz (Material religion, 2018)
This paper examines the spatial relations between the principal public squares in Latin Famagusta and the architecture of the major Latin and Greek churches which dominated them. The study uses historical and archaeological records to reconstruct parts of fourteenth-century Famagusta's urban layout and uses a method called perspectival logic to demonstrate that the plan of the city's streets and piazzas was not a result of chaotic, ad hoc decisions. Rather, it was consciously designed to shape the lived experience of those present in the city. It enforced social hierarchies and created public spaces that addressed the commercial and religious needs of the city's diverse urban society. Pedestrians crossing Famagusta's piazzas were offered favorable views of religious monuments, which strengthened the public reception of the religious messages conveyed through their architecture. The shape of each piazza facilitated the fluency of pedestrian movement and manipulated its direction, so that areas located close to external galleries of Famagusta's churches were secluded from daily traffic. This made these spaces suitable for outdoor preaching, on occasions such as St. Bridget of Sweden's delivery of public sermons to the inhabitants of Famagusta in 1372.